Pseudo-Patriarki dalam Kitab Uqūd al-Lujjayn: Analisis Kritis atas Tuduhan Bias Gender terhadap Syekh Nawawi al-Bantani - Azis Faturokhman; Hikmatullah Hikmatullah; Hapizul Ahdi (STIKes Ibnu Sina Ajibarang, 2025)
The book Uqūd al-Lujjayn fī Bayān Ḥuqūq az-Zaujayn by Sheikh Nawawi al-Bantani is one of the classical texts that is very popular among Islamic boarding schools and the Muslim community of the archipelago. However, in contemporary discourse, this book is often the target of criticism from Muslim feminists who accuse it of being full of gender bias and patriarchal. This criticism arises because of discussions about the wife's obligation to obey her husband, the prohibition of leaving the house without permission, and the husband's permissibility to reprimand his wife who is considered nusyūz. This paper attempts to conduct a philological and hermeneutic analysis of the text Uqūd al-Lujjayn by reviewing the historical, methodological, and fiqh reference sources of Sheikh Nawawi al-Bantani. This study found that the patriarchal character in the book is pseudo (pseudo), not ideological. Sheikh Nawawi actually wrote this book within the tradition of Islamic jurisprudence (fiqh akhlaqiyyah), not as a legitimation of male power over women. Through a philological approach, it was found that the text's structure and selection of hadith in this book aimed to educate household morals, not to reinforce the patriarchal system. Therefore, accusations of gender bias against Sheikh Nawawi require methodological reexamination to avoid falling into ahistorical ideological readings.